The Basis on which to build the Physical Education of School Children (Fiep Bulletin - online, 2015)
Physical education is as old as civilization itself and its needs are always related to the progress of the latter, although they are not yet totally defined. Day by day physical education in becoming more important as a means of improvement both individually and collectively in the civilized world.
Keywords: .